Immunotherapy Combined With Radiation Therapy for Genitourinary Malignancies - Ukleja, Jacob; Kusaka, Erika; Miyamoto, David T. (Frontiers in Oncology, 2021)
Immunotherapy drugs have recently been approved by the Food and Drug Administration for the treatment of several genitourinary malignancies, including bladder cancer, renal cancer, and prostate cancer. Preclinical data and early clinical trial results suggest that immune checkpoint inhibitors can act synergistically with radiation therapy to enhance tumor cell killing at local irradiated sites and in some cases at distant sites through an abscopal effect. Because radiation therapy is commonly used in the treatment of genitourinary malignancies, there is great interest in testing the combination of immunotherapy with radiation therapy in these cancers to further improve treatment efficacy. In this review, we discuss the current evidence and biological rationale for combining immunotherapy with radiation therapy, as well as emerging data from ongoing and planned clinical trials testing the efficacy and tolerability of this combination in the treatment of genitourinary malignancies. We also outline outstanding questions regarding sequencing, dose fractionation, and biomarkers that remain to be addressed for the optimal delivery of this promising treatment approach.